Description Of Education And Its Impact On Distress Among Hemodialysis Patients': Literature Review - Pulo, Eldad Onesiforus Sopater; Astuti, Dwi; Boli, Elisabet Bre; Jober, Naomi F; Sasarari, Zusana A; Watunglawar, E (Jurnal Ners, 2025)
Chronic Kidney Disease (CKD) has become a significant health problem in developing and underdeveloped countries in Southeast Asia (including Indonesia). The high cases of CKD patients undergoing hemodialysis (HD) can also increase the incidence of distress. Interventions in providing education are essential to a series of therapies to deal with distress. The purpose of this review is to have an overview of providing education and its impact on the distress of CKD patients undergoing HD. The search for articles in this review was conducted on the PubMed, Science Direct, and EBSCO databases. The search was conducted based on a combination of Boolean and keywords (Chronic Kidney Disease OR Renal Failure OR End-Stage Renal Disease OR Hemodialysis Patient) AND (Stress OR Distress) AND (Education OR Health Education OR Health Promotion). All articles were analysed according to the stages in the PRISMA flowchart. There are 12 articles selected based on the criteria. The 12 articles analyzed the interventions: CBT, MI, psychoeducation, oral and video education, psychological training, supportive-expressive group therapy, educational-supportive group therapy, hope therapy, and empowerment programs. Because there are similarities in concept and content, some interventions are grouped into psychoeducational interventions. CBT is the most widely used and effective educational intervention in dealing with the distress of HD patients, especially those related to anxiety and depression. Several types of psychoeducational programs can be used to treat psychological distress, especially those related to depression and anxiety in HD patients.